Efficacy of Autologous Platelet-Rich Plasma Therapy in Chronic Non-Healing Ulcers of the Lower Limb - Dr. Samir M. Kacheriwala,; Dr. Anurag S. Yadav,; Dr. Kartik K. Agrawal,; Dr. Jinal Patel,; Dr. D. Yashwanth Krishna, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Chronic lower-limb ulcers are a global health burden that resist conventional care and impair quality of life. Autologous platelet-rich plasma (PRP) delivers supra-physiological concentrations of growth factors that may accelerate tissue regeneration and reduce time-to-heal. Methods: In this prospective, randomised controlled study, 60 adults (30 PRP; 30 controls) with chronic (> 6 weeks) lower-limb ulcers measuring 2–50 cm² were followed for 12 weeks. The PRP group received weekly autologous PRP injections and topical application after thorough debridement, whereas controls received identical wound preparation followed by sterile saline dressing. Primary outcomes were percentage reduction in ulcer area and complete epithelialisation rate; secondary outcomes included granulation quality, colour score, bacteriological clearance and time-to-heal. Results: Baseline characteristics (age 52 ± 11 vs. 48 ± 11 y; p = 0.12) and ulcer size (14.8 ± 7.1 vs. 16.2 ± 6.2 cm²; p = 0.27) were comparable. Mean ulcer-area reduction at week 4 was 48.7 % in PRP vs. 26.1 % in controls (p < 0.001) and at week 8 was 81.6 % vs. 52.7 % (p < 0.001). Complete healing within 12 weeks occurred in 80 % of PRP-treated ulcers versus 46.7 % of controls (RR 1.71, 95 % CI 1.10–2.66). Median healing time was 7.5 weeks (IQR 6–9) with PRP and 10.5 weeks (IQR 9–12) with standard dressing (p < 0.001). Granulation and colour scores improved significantly earlier in the PRP arm (week 4, p < 0.001). Positive bacterial cultures fell from 73.3 % to 6.7 % in PRP wounds versus 83.3 % to 13.3 % in controls by week 12 (p = 0.045). No significant adverse events were recorded. Conclusion: Weekly autologous PRP therapy significantly accelerates healing trajectories, enhances granulation, and shortens time-to-closure in chronic lower-limb ulcers without added morbidity. Integrating PRP into multidisciplinary wound protocols could reduce healthcare utilisation and amputation risk.